The Ideological Foundations of Universal and Exclusive Solidarity in Austria - Schadauer, Andreas; Flecker, Jörg (Momentum Quarterly, 2023)
Solidarity is a term and concept many appeal to, especially during crises. It also enjoys a long tradition within social sciences but nevertheless remains a rather ambiguous term with many open questions attached. Based on theoretical literature, this article introduces a multidimensional empirical concept of solidarity by combining opinions regarding global, institutional, group-oriented, and supportive dimensions of solidarity, or a lack thereof. This allows for differentiation between two publicly and politically discussed and contested types of solidarity: universal and exclusive solidarity. The article then further addresses what influences the Austrian (survey) population’s preferences regarding these types of solidarities, with a focus on ideologies. This is empirically tested via survey data and multiple linear regression models. This approach allows for closing an existing gap between the theoretical and empirical literature and for more thoroughly examining the relation between solidarity and the perception of groupings and belongings. The latter is necessary to contrast the different types of solidarity.